Residents’ perception of housing quality index for dwellings’ physical characteristics in the core area of Ado-Ekiti, Nigeria - Omoniyi, Sunday Samuel; Odufuwa, Bashir Olufemi; Uzzi, Festus Osarumwense (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines residents’ perception of housing quality index for dwellings’ physical characteristics in the core area Ado-Ekiti, Nigeria, South-west Nigeria. A survey of 602 households randomly selected from the core area was done. The results of the study revealed that more than half of the respondents indicated that the present condition of the dwellings components like (roofs, walls, windows, floors, foundations and fascia boards) in the study area was in a very bad state. Subsequently, housing quality index (H.Q.I) for the entire sample was evaluated and the housing quality indexes results were found to be below average (fair) using a five-point Likert scale, starting from very bad (rated as 1), fair (rated as 3) to very good (rated as 5) to calculate the total weighted values of all rated attributes and means values of rated attributes in the study area. Surveyed results have shown significant deterioration in quality of dwellings components in the core area, due to age of buildings and lack of maintenance. The study concluded that there is an urgent need to replace the bad dwellings components, build new structures, provides basic amenities like electricity, pipe-borne water, roads/drainages and to refurbish the existing ones to ensure that the residents do not lack all these amenities.